Biomarker-Based Prediction of Survival and Recovery of Kidney Function in Acute Kidney Injury - Daniel Patschan; Stefan Erfurt; Stefanie Oess; Martin Lauxmann; Susann Patschan; Oliver Ritter; Meike Hoffmeister (Karger Publishers, 2023)
Background: Acute kidney injury (AKI) affects increasing numbers of hospitalized patients; the prognosis remains poor. The diagnosis is still based on the 2012 published KDIGO criteria. Numerous new AKI biomarkers have been identified in recent years; they either reflect impaired excretory function or structural damage. The majority of markers are useful for AKI recognition under certain circumstances. Fewer data are available on the role of biomarkers in the prediction of in-hospital survival and renal recovery post-AKI. The current article is intended to provide information about these two aspects. Summary: The following databases were screened: PubMed, Web of Science, Cochrane Library, Scopus. The period lasted from 2000 until 2022. The following terms were applied: "AKI" AND "biomarker" AND "survival" OR "mortality" OR "recovery of kidney function" OR "renal recovery" OR "kidney recovery". The following terms were used for additional literature search: "TIMP-2" AND "IGFBP7" and "RNA biomarker" AND "hematology". Regarding mortality, exclusively those studies were selected that addressed the in-hospital mortality. Nine (9) studies were identified that evaluated biomarker-based prediction of in-hospital mortality and/or of recovery of kidney function (ROKF). A homogenous definition of ROKF is however missing yet. Currently, some biomarkers, measured early during the course of the disease, are associated with increased mortality risk and/or with a higher chance of renal recovery. Key Messages: The literature provides only a few biomarker-related studies that address the issues of mortality and recovery. The definition of ROKF needs to be homogenized.